Very Happy People - Diener, Ed; Seligman, Martin E.P. (Psychological Science, 2002)
A sample of 222 undergraduates was screened for high happiness using multiple confirming assessment filters. We compared the upper 10% of consistently very happy people with average and very unhappy people. The very happy people were highly social, and had stronger romantic and other social relationships than less happy groups. They were more extroverted, more agreeable, and less neurotic, and scored lower on several psychopathology scales of the Minnesota Multiphasic Personality Inventory. Compared with the less happy groups, the happiest respondents did not exercise significantly more, participate in religious activities significantly more, or experience more objectively defined good events. No variable was sufficient for happiness, but good social relations were necessary. Members of the happiest group experienced positive, but not ecstatic, feelings most of the time, and they reported occasional negative moods. This suggests that very happy people do have a functioning emotion system that can react appropriately to life events.